Govt focused on ensuring IPTA among world's best - New Sabah Times English, (KK) (New Sabah Times English, 2013)
KllALA LUMPUR: The education ministry has outlined six strategies to boost the performances of public institutions of higher learning (IPTA) and their positions in the world. Deputy Education Minister Datuk Mary Yap Kian Ching said the move was in line with the aspiration of the government in the National Higher Education Strategic Plan targeting three local universities for recognition as among the 100 best in the world, and, one among them, to be in the top 50, by 2020.